A bibliometric mapping of cost-benefit analysis: Three decades of studies - Ingrid Majerova; Ainur Abdrazakova (Economies, 2021)
Over time, the cost-benefit analysis has become a method that helps to clarify the pros and cons in many areas of human activity where both investment and non-investment projects are implemented. In researching for this article, we aimed to map the current state of publishing activities in the field of cost-benefit analysis and in order to accomplish this, four research questions had to be determined. For this purpose, the outputs indexed in the database Web of Science Clarivate Analytics were examined and the method of bibliometric analysis within the VOSviewer software was used. It was ascertained that almost six hundred outputs had been published: almost all of them were published in English and generated by more than sixty percent of authors from English-speaking countries. Cost-benefit analysis was most often used in the areas of healthcare, environment and ecology, and economics and social sciences. In terms of co-authorship, it was found that there had been a shift from collaboration among authors from Israel and English-speaking countries to cooperation between mostly Chinese authors and authors from Northern Europe. In the case of co-occurrence, three clusters were identified: the most frequent was the area of terms related to economic financial analysis, the second area was related to health issues, and the third was related to the process of cost-benefit analysis' application.
Keywords: 330; bibliometric analysis; co-authorship; co-occurrence; cost-benefit analysis; visualization